Complaint from art. 189 of The Code of Civil Procedure in the event of defective resolutions of a supervisory board of a company - Jaros, Paweł (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The aim of this paper is to present the issue of using a complaint from article 189 of The Code of Civil Procedure to challenge resolutions of a supervisory board of a company. This matter is not regulated precisely in The Code of Commercial Companies. According to the majority of representatives of Polish doctrine the complaint from article 189 of The Code of Civil Procedure is the most proper resource to repeal defective resolutions of a supervisory board in the current legal system. Nevertheless, the above fact does not mean that the declaratory action is deprived of any defects. On the contrary, it has certain weaknesses, which might play an important role in corporate relationships. Therefore, according to The Author, it becomes necessary to provide adequate legal regulations in the issue of challenging resolutions of a supervisory board of a company.